Pengaruh Digitalisasi Pengelolaan Zakat Terhadap Peningkatan Partisipasi Muzakki - Rival Rinaldi; Romi adetio Setiawan; Syaifuddin Syaifuddin (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2026)
This study aims to determine the effect of zakat management digitalization on the increase in muzakki (zakat payer) participation at BAZNAS (National Zakat Agency) of Bengkulu Province. The research was motivated by the growing need to utilize digital technology to enhance the efficiency and effectiveness of zakat management. A quantitative approach with an associative descriptive method was employed. Data were collected through observation, documentation, and questionnaires distributed to 30 muzakki who had used BAZNAS's digital services. Data analysis was conducted using the Partial Least Square (PLS) method with the SmartPLS software. The findings revealed that the digitalization of zakat management does not have a significant effect on increasing muzakki participation. This indicates that although digital systems have been implemented, they are not sufficient on their own to boost participation. Other factors such as trust, digital literacy, and personalized or educational approaches may have a more substantial impact. The study recommends that BAZNAS improve its communication strategies, digital education, and community engagement to maximize the effectiveness of digital platforms.